Clinical and anatomopathological study of urolithiasis in feedlot lambs subjected to diets with different phosphorus concentrations - Santarosa, Bianca Paola; Ferreira, Danilo Otávio Laurenti; Surian, Soraya Regina Sacco; Tremori, Tália Missen [UNESP]; Hooper, Henrique Barbosa; Dos Santos Silva, Priscila; Coelho, Matheus Ribeiro; Dos Santos, Vítor Hugo; Gonçalves, Roberto Calderon [UNESP] (FapUNIFESP (SciELO), 2021)
Obstructive urolithiasis is common in farmed sheep and has a multifactorial etiology, but inadequate nutritional management is considered the most relevant condition for its occurrence. The objectives of this study were to verify the influence of two diets with different concentrations of calcium (Ca) and phosphorus (P) on the development of obstructive urolithiasis, and to describe the clinical and anatomopathological findings of the urinary system in sheep. Thirty male crossbred Santa Inês and Ile de France lambs were randomly distributed into two groups: Group 1 (G1, n = 15) – Ca: 1.9:1 P and 0.42% P; Group 2 (G2, n = 15) – Ca: P 1.5:1 and 0.65% P. The diets consisting of Coast-cross hay, soybean meal, wheat, and corn were provided for 90 consecutive days with water ad libitum. After the diagnosis of the disease, the lambs were subjected to clinical and surgical treatment, when necessary. Urolithiasis was detected in 36.7% (11/30) of lambs, 26.7% were asymptomatic and 10% (3/30) had urethral obstruction. A lamb was unobstructed after amputation of the urethral process and urethral catheterization, one died of bladder and uroperitoneum rupture, and another was sacrificed after the failure of perineal urethrostomy and cystostomy. The most frequent renal histopathological changes were vascular congestion, dilation, and tubular degeneration. Proteins in the tubular lumen were more pronounced in G2. The diets were rich in concentrate and had adequate Ca:P ratios, but caused calculogenesis, showing that excess minerals and a small amount of roughage can cause disease in the herd.
Estudo clínico e anatomopatológico da urolitíase em cordeiros confinados submetidos à dieta com diferentes concentrações de fósforo
Keywords: Feedlot; Phosphorus; Sheep; Urethral obstruction; Urolith